Motivation learning achievement in open distance learning (ODL) environment: skills, beliefs, self-direction and interaction of university students / Ahmad Fikri Mohd Kassim, Farhana Sardon and Ellail Ain Mohd Aznan - Mohd Kassim, Ahmad Fikri; Sardon, Farhana; Mohd Aznan, Ellail Ain (Universiti Teknologi MARA, Perlis, 2022)
The COVID-19 pandemic in Malaysia has seen the number of positive carriers rise day by day, prompting the government to issue a movement control order (MCO), compelling Malaysians to stay at home to prevent the virus from spreading quickly in the year 2020-2021. The MCO has an impact on students. This situation forces them to stay at home while the learning process continues in Online Distance Learning (ODL) mode. The institution is concerned about the implications of online learning as a teaching technique that is intended to improve students' academic performance by increasing computer self-efficacy and other factors such as student satisfaction and e-learning outcomes. Therefore, this study aims to examine the motivation learning achievement in ODL among university students. A total of 290 volunteer students of both genders with diploma and bachelor degrees students participated in this study. The study found that there were significant relationships between the factors of motivation learning achievement. There were differences in motivation learning achievement (skills, beliefs, self-direction and interaction) between genders. Whilst, there were no significant differences in the factors of motivation learning achievement (skills, beliefs, self-direction and interaction) between diploma and bachelor degree students. Thus, the ODL appears to be new standards that should not obstruct potential interactive learning for optimal academic performance and accomplishment. In other words, this research provides a new perception to lecturers, faculty management, and the institution, as well as serving as the standard practice of ODL in the future